Animaland - Hand, David; Felstead, Bert (image Entertainment, 1998)
Lost for nearly fifty years, this collection contains nine animated short stories produced by David Hand, one of the creative talents behind such legendary Disney features as "Snow White" and "Fantasia." [www.amazon.com]
Keywords: DVD-Video